Water-soluble CMY primary color electrochromic polymers: design, synthesis and full color control. Issue 4 (4th January 2022) - Dai, Dacheng; Ouyang, Mi; Zhang, Lina; Fu, Haichang; Tao, Bowen; Li, Weijun; Lv, Xiaojing; Bai, Ru; Dong, Yujie; Zhang, Cheng
Abstract : The next generation of electrochromic materials are required to be rich in color rendering, offer excellent processability and contribute to environmental protection. Abstract : The next generation of electrochromic materials are required to be rich in color rendering, offer excellent processability and contribute to environmental protection. Soluble electrochromic polymers (ECPs) can fulfill these requirements. However, a more environmentally friendly water-soluble ECP (WS-ECP) primary color system has not yet been developed. In this work, three novel 3, 4-propylenedioxythiophene (ProDOT)-based and colored-to-transmissive ECPs that could be processed from aqueous solutions were designed and synthesized, referred to as WS-ECP-Cyan (WS-ECP-C), WS-ECP-Magenta (WS-ECP-M), and WS-ECP-Yellow (WS-ECP-Y), respectively. All three WS-ECPs exhibit desirable electrochromic properties, including fast switching speed (1.39 s/0.57 s for WS-ECP-Y), appropriate optical contrast (54.4% for WS-ECP-M) and lasting cycle stability (1.5% reduction for WS-ECP-C after 100 cycles) with low driving voltages (<0.8 V). Subsequently, according to the CMY color mixing theory, a range of multilayer films, with the help of the polymer solubility changes (soluble/insoluble) caused by the side chain transformation of WS-ECPs, were formed onto ITO-coated glass through spraying layer by layer (SLbL) to realize full color control. In the same way, all colors in the visible spectrum including black color were also achieved via the co-processing of multicomponent WS-ECPs. The resulting ECP composite films (SLbL or co-processing) showed electrochromic properties comparable to those of WS-ECP-C/M/Y films. The establishment of an environmentally friendly WS-ECP primary color system and two color control methods (SLbL and co-processing) that can realize full color control will strongly promote the application of electrochromic materials in various fields of people's daily life.